Tomato production in response to doses of silicon - Cazárez-Flores, Luz Llarely; Angulo-Castro, Azaree; Vega-Gutiérrez, Tomás Aarón; Ayala-Tafoya, Felipe; Aguilar- Quiñonez, José Antonio (Ecosistemas y Recursos Agropecuarios, 2023)
There is evidence about the improvement of plant resistance to biotic and abiotic factors, photosynthetic metabolism, and crop productivity by silicon fertilization. The objective of the research was to know the influence of silicon on the growth, yield, and postharvest quality of indeterminate saladette tomato grown in soil. A randomized complete block design was used with four treatments (0/control, 20, 30 and 50 mg L-1 of silicon) and three repetitions. The three doses of silicon under study were effective in increasing stem diameter, number of leaves, leaf area, greenness index, and titratable acidity. The firmness and soluble solids content of the fruit were not affected. While, with the dose of 50 mg L-1 the highest tomato yield was induced. In general, tomato production improved significantly with the addition of silicon to the fertilization scheme.
Keywords: °Brix, firmness, greenness, growth, yield.